Investigating Dissolved Organic Matter Dynamics in the Downstream Reaches of the Ganges and Brahmaputra Rivers Using Fluorescence Spectroscopy - Niloy, Nahin Mostofa; Shammi, Mashura; Haque, Md. Morshedul; Tareq, Shafi M. (Frontiers in Earth Science, 2022)
The Ganges and the Brahmaputra, two major rivers in Bangladesh contribute major loads of dissolved organic matter (DOM) into the Bay of Bengal. The composition, sources, availability and seasonal heterogeneity of DOM in these two rivers are thus very important to know about the biogeochemical cycles, fate and ecological and environmental aspects before discharge into the Bay of Bengal. In this study, DOM was characterized in the downstream reaches of the Ganges and Brahmaputra rivers before their confluence with each other. The concentration of dissolved oxygen decreased in the pre-monsoon and monsoon in both rivers due to the increased decomposition and oxidation of rainfall washed substances and thus made the water unsuitable for drinking purpose. The amount of total coliform also made the both rivers water unsuitable for the drinking, recreational and irrigation purposes. Four DOM components (one humic, one detergent- and two protein-like) in the Ganges River and five DOM components (three humic- and two protein-like) in the Brahmaputra River were identified at their downstream reaches using fluorescence spectroscopy, three dimensional excitation emission matrix (EEM) measurement and parallel factor analysis (PARAFAC). The abundances of DOM components were higher in the pre-monsoon and monsoon seasons than the post-monsoon season. Protein-like components contributed the most in two rivers. DOM were mostly from terrestrial sources, were matured and less aromatic. This study also identifies that sewage water is the largest contributor to DOM in surface water, next to natural sources, and indicates the excessive anthropogenic activities in the river basins of Bangladesh.